2009
DOI: 10.1093/icb/icp057
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic integration and independence: Hormones, performance, and response to environmental change

Abstract: Hormones coordinate the co-expression of behavioral, physiological, and morphological traits, giving rise to correlations among traits and organisms whose parts work well together. This article considers the implications of these hormonal correlations with respect to the evolution of hormone-mediated traits. Such traits can evolve owing to changes in hormone secretion, hormonal affinity for carrier proteins, rates of degradation and conversion, and interaction with target tissues to name a few. Critically, how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
219
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(225 citation statements)
references
References 92 publications
3
219
3
Order By: Relevance
“…This result strongly suggests that sensitivity to plasma steroid manipulations differs between the morphs. Other authors have suggested that steroid-sensitive behaviors are often better correlated with steroid receptors than with plasma steroid levels (10,11,(32)(33)(34). In dark-eyed juncos (Junco hyemalis), a relative of white-throated sparrows, aggressive responses to STI were positively correlated with ERα mRNA expression in the ventral telencephalon, which contains MeA, and negatively correlated with it in the hypothalamus (11).…”
Section: Discussionmentioning
confidence: 99%
“…This result strongly suggests that sensitivity to plasma steroid manipulations differs between the morphs. Other authors have suggested that steroid-sensitive behaviors are often better correlated with steroid receptors than with plasma steroid levels (10,11,(32)(33)(34). In dark-eyed juncos (Junco hyemalis), a relative of white-throated sparrows, aggressive responses to STI were positively correlated with ERα mRNA expression in the ventral telencephalon, which contains MeA, and negatively correlated with it in the hypothalamus (11).…”
Section: Discussionmentioning
confidence: 99%
“…Because of the link between environmental cues and the resulting phenotype, hormones have been suggested to be critical in shaping evolution to changing environments. However, a single hormone can affect the expression of multiple traits (physiological epistasis, [44,51] or hormonal pleiotropy, [52], hence selection acting on one trait may be constrained by the underlying correlational structure with other traits. In particular, when the covariation between a trait and fitness is conditional on several traits, selection acting on a trait is correlational; the magnitude and direction of selection coefficients depend on the product of two traits.…”
Section: Hormonal Effects On Components Of Fitnessmentioning
confidence: 99%
“…Phenotypic integration that arises from hormonemediated expression of correlated traits has been implied to present limited opportunity for rapid evolution in response to climate-change scenarios [52]. However, phenotypic integration does not necessarily suggest phenotypic rigidity [151].…”
Section: Hormonal Effects On Components Of Fitnessmentioning
confidence: 99%
“…Hendry et al (2008) undertook a metaanalysis of over 3000 rates of recent phenotypic change in 68 systems and found that rates of phenotypic change are greater in anthropogenic contexts than in natural contexts. Research to date has focused heavily on phenotypic plasticity in the context of reproduction, including competition and selection of mates, as well communication (for reviews, see Brown 2012;Ketterson et al 2009;Lowry et al 2013;Sol et al 2013;Wong and Candolin 2015).…”
Section: Introductionmentioning
confidence: 99%